Applications of three-dimensional surgical planning in facial feminization surgery: A systematic review. Issue 7 (July 2022) - Escandón, Joseph M.; Morrison, Clinton S.; Langstein, Howard N.; Ciudad, Pedro; Del Corral, Gabriel; Manrique, Oscar J.
Summary: Background: Despite some reports that have shown an increase in safety, efficiency, and accuracy during feminizing craniofacial procedures utilizing three-dimensional (3D) technology, there are no reports summarizing the available evidence on this matter for facial feminization surgery (FFS). Here, we aimed to systematically review the application of 3D technology on FFS. Methods: We conducted a comprehensive search across PubMed, SCOPUS, Ovid MEDLINE®, Web of Science, and ScienceDirect looking for studies reporting the use of 3D surgical planning in the setting of FFS following the PRISMA guidelines. We extracted data on photographic assessment, imaging, surgical application, and surgical technique and outcomes. Results: This review included 10 studies comprising 1473 transgender female patients and 50 cadaveric cranial specimens. Four studies employed virtual surgical planning (VSP) and the concomitant use of prefabricated cutting guides. One study reported the implementation of 3D VSP using a female skull as a reference. One study used computer-aided design cutting guides and custom plates for FFS. Standardized incorporation of 3D printed models allowed for preoperative planning in three studies. Three studies reported VSP using 3D reconstruction of CT images, but without the use of 3D printing. Three studies used 3D photography with specialized camera technology to enrich clinical documentation and provide a comprehensive facial analysis of soft tissue. Accuracy ranged from 85.7% to 97%. Morbidity ranged from 0% to 12.5%. Conclusion: Based on this data, we believe 3D VSP has promising outcomes in terms of accuracy and low morbidity, encouraging its implementation in FFS. However, further prospective double-arm cohort studies are required.